Penerapan Ular Tangga “Paham Dengan Diri” Sebagai Media Interaktif dalam Layanan Bimbingan Konseling - Fadilah, Firda Nurul (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the results of implementing the PADEDI (Understanding Oneself) snakes and ladders game as an interactive medium in group-based counseling services for seventh-grade students of Khodijah Class. This research is a classroom action study, with data collected through observation, interviews, and documentation involving the students of Khodijah Class. The findings indicate that the PADEDI snakes and ladders game can be utilized as an interactive learning tool to assist students in understanding themselves. The media consists of cards, a game board, and other components designed to support the concept of self-awareness. In the first cycle, several indicators of feasibility were not achieved, with success rates below 80-90%, the benchmark for the media's feasibility. However, after the implementation in the second cycle, all research indicators met the feasibility criteria, achieving a success rate of 80-90%. Thus, the PADEDI snakes and ladders game is effective for use in group-based classical learning processes.